Friendship and Positive Peace: Conceptualising Friendship in Politics and International Relations - Hoef, Yuri van (2018)
In recent years, the study of friendship has gained traction in political science. The aim of this article is threefold: (1) to offer an overview of the status of friendship studies and how it relates to the emotional turn in international relations, (2) to present a wide variety of different approaches to studying friendship, and (3) to highlight the contribution that a friendship perspective can make to other fields, such as Peace and Conflict Studies. From Aristotle and Plato onwards, we trace the development of the concept of friendship, and present several theoretical conceptualisations and methodological approaches that can be readily applied when making sense of friendship, both on a personal level between elite actors, and on the international level between states. We end by drawing attention to the merit of the study of friendship specifically for the field of Peace and Conflict Studies, where it helps to address the lacuna of research on positive peace.